2022
DOI: 10.1007/s00784-022-04628-1
|View full text |Cite
|
Sign up to set email alerts
|

Short versus standard implants at sinus augmented sites: a systematic review and meta-analysis

Abstract: Background Short implants are proposed as a less invasive alternative with fewer complications than standard implants in combination with sinus lift. The aim of this systematic review and meta-analysis was to state the efficacy of placing short implants (≤ 6 mm) compared to standard-length implants (≥ 8 mm) performing sinus lift techniques in patients with edentulous posterior atrophic jaws. Efficacy will be evaluated through analyzing implant survival (IS) and maintenance of peri-implant bone (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(136 reference statements)
0
7
0
2
Order By: Relevance
“…In the analysis, the authors included implants inserted in the mandibular region. In the meta-analysis of Toledano and coworkers [ 22 ], the authors included RCTs with a follow-up longer than 1 year with a RR value of 1.02 [95% CI: (1.00, 1.05); p = 0.09], suggesting that the ISR was similar for both types of implants. The meta-analysis of Bitinas et al [ 9 ] included 3 RCTs with a follow-up of 5 years and also showed a statistically insignificant difference with a RR value of 0.03 [95% CI: −0.07 to 0.13, ( p = 0.52)].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the analysis, the authors included implants inserted in the mandibular region. In the meta-analysis of Toledano and coworkers [ 22 ], the authors included RCTs with a follow-up longer than 1 year with a RR value of 1.02 [95% CI: (1.00, 1.05); p = 0.09], suggesting that the ISR was similar for both types of implants. The meta-analysis of Bitinas et al [ 9 ] included 3 RCTs with a follow-up of 5 years and also showed a statistically insignificant difference with a RR value of 0.03 [95% CI: −0.07 to 0.13, ( p = 0.52)].…”
Section: Discussionmentioning
confidence: 99%
“…Other RCTs have indicated that the ISR for both implants are the same [ 25 , 26 ]. These inconsistencies around systematic reviews may be due to the study population and type of implant system used [ 22 ]. However, standard implants with sinus lifts showed better outcomes, and the sinus lift procedure still remains a sensitive technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications might be associated with sinus floor elevation [ 33 ]. Short implants have been shown to represent a valid alternative, exhibiting lower marginal bone loss compared to standard-length implants and similar survival rate [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Teeth loss in the posterior region may leads an alveolar bone resorption associated with maxillary sinus' pneumatization. These conditions may present vertical bone defects that make rehabilitation with osseointegrated implants impossible or difficult [2]. To overcome these conditions, new implant geometries allow their stability in minimal bone remnants and the development of new surfaces favor osseointegration, minimizing the stability drop between primary and secondary stability [3,4].…”
Section: Introductionmentioning
confidence: 99%